MIRERC 072/2025: Prevalence and Genotype Distribution of High-risk HPV Among Women in Ghana and Kenya - Onyambu, Dr. Frank; Yaw Bediako, PhD; Eliza Mari Kwesi-Maliepaard; Dr. Emmanuella Amoako; Nasteha Issack; Celestine Kemunto, (MUST Institutional Research Ethics Review Committee (MIRERC), 2025)
Abstract Background: The burden of cervical cancer is highest in Africa. HPV infection is the major cause of cervical cancer. There are over 200 different HPV genotypes, with 15 considered (potential) high-risk genotypes for developing cancer. Due to lack of systematic screening programs in most African countries there is limited data available on which HPV-genotypes are most prevalent in the population. Methods: We want to analyze a database of HPV-genotyping data from cervical samples submitted for diagnostic HPV-genotype testing. We have data available from HPV genotyping in Ghana (n = 1451) and Kenya (n = 46). The data will be analyzed to assess the prevalence of HPV infection in this database and to determine the distribution of high-risk HPV genotypes. Expected outcome and implications: We expect that the outcomes from our analysis of the HPV genotyping data will contribute to a better understanding of HPV infection in African women. This will also help to inform decision making on HPV screening and HPV vaccination strategies.